The Idea of War in the Culture of the Russian Nation - Piotr Gawliczek; Jacek Mrozek; Andrzej Soboń (Polish Political Science Yearbook, 2025)
Mentality is the result of social processes and is shaped by life experiences, as well as values and norms passed on during socialization. In the case of Russia, history, literature, art, and spirituality play a significant role in shaping the national identity and, consequently, the perception of war. The image of war is often presented in a selective or idealized way. In Russian historical discourse, the positive aspects of one’s history are often emphasized, while, simultaneously, controversial or negative factors are often ignored or minimized. The methodology employed in the paper involves a qualitative comparative method, which involves analyzing the concept of war in Russian culture, describing the characteristics of a nation’s mentality through various aspects of an ethnic group’s spiritual life, and understanding the ideology underlying Russia’s foreign policy. The article concludes that analyzing the concept of war within the Russian nation’s culture is not possible without understanding the general mentality of the entire society. The Russians are less willing to take up the problem of crimes committed in that period by soldiers of the Red Army, which is also the case during the occupation of Ukraine.